Relating wave attenuation to pancake ice thickness, using field measurements and model results. Issue 11 (9th June 2015) - Doble, Martin J.; De Carolis, Giacomo; Meylan, Michael H.; Bidlot, Jean‐Raymond; Wadhams, Peter
Abstract Wave attenuation coefficients (α, m−1) were calculated from in situ data transmitted by custom wave buoys deployed into the advancing pancake ice region of the Weddell Sea. Data cover a 12 day period as the buoy array was first compressed and then dilated under the influence of a passing low‐pressure system. Attenuation was found to vary over more than 2 orders of magnitude and to be far higher than that observed in broken‐floe marginal ice zones. A clear linear relation between α and ice thickness was demonstrated, using ice thickness from a novel dynamic/thermodynamic model. A simple expression for α in terms of wave period and ice thickness was derived, for application in research and operational models. The variation of α was further investigated with a two‐layer viscous model, and a linear relation was found between eddy viscosity in the sub‐ice boundary layer and ice thickness.